An overview of Inuit perspectives on Franklin’s lost expedition (1845–1846): a few avenues for discussion and future research – commentary to Pawliw, Berthold, and Lasserre - Mossé, Marie (Fennia - International Journal of Geography, 2021)
International audience This reflection deals with the role Inuit knowledges and oral history played in the discovery of Franklin expedition’s shipwreck at the turn of the 2010s and, more specifically, with the process through which those knowledges were finally taken into account by Canadian political and scientific institutions as well as medias and public opinion. I aim to highlight the fundamental ambivalence of this process and to address the questions whether and how it finds its place in the global context of Canadian Reconciliation process, and why it contributes to “recomplexify” the Canadian and Western representation of Arctic.